MCQs in pharmacology - Kulkarni, Jayant S; Jayant S.Kulkarni (New Delhi, CBS., 2007)
"Pharmacology is the study of substances that interact with living systems through chemical processes, especially by binding to regulatory molecules and activating or inhibiting normal body processes. If substances have medicinal properties, they are considered drugs or pharmaceuticals. The field encompasses drug composition and properties, interactions, toxicology, therapy, and medical applications and antipathogenic capabilities. Pharmacology lies at the heart of biomedical science, linking together pharmaceutical chemistry, physiology, and pathology. Comprehensive MCQs in Pharmacology represents copious multiple choice questions, which can be used to assess essential pharmacology knowledge that equips pharmacists with exclusive perceptions and acumens in the provision of pharmaceutical care. It also provides a brief account of recent perspectives in drug research, as either a study or high-yield revision aid. This book is suitable for professionals, academicians, students, researchers, scientists and industrialists around the world in the fields of pharmacology and pharmaceutical sciences. Furthermore, for pharmacy preregistration examination candidates and for practicing pharmacists, this book is a storehouse of knowledge. The organization of this book provided a profound knowledge and also maintains the reader's interest"--